The Research of Declining Factor and a New Model of Decline Rate for Gas Well Production in Low Permeability Reservoir - Wang, Hua; Wu, Yong; Fu, Yu; Zhang, Yunjun (Frontiers in Physics, 2022)
The decline rate of gas wells varies with production time and is related to reservoir and working system. A typical single well numerical model of low permeability gas wells is established. The variation law of decline rate and its main influencing factors are studied by single factor analysis method. The results show that there are two stages of rapid and slow decline for the decline rate of gas wells, and the decline rate tends to be stable after the gas wells entering the decline period of 2-3 years; the decline rate increases with the increase of permeability, gas saturation and wellhead pressure, and decreases with the increase of porosity and well-controlled reserves; the decline rate in late production does not change with the change of reservoir thickness, initial production allocation and formation pressure. Then the decline rate model is and Then the decline rate model and the non-linear model of each factor are established by using response surface method are used to predict the decline rate quickly and accurately. According to the prediction model, the larger the well-controlled reserves, the smaller the permeability and the smaller the decline rate. In order to reduce production decline rate in gas well production process, it is suggested that the influence of various parameters on production decline rate should be considered comprehensively, and the well-controlled reserves of gas well should be increased as far as possible.